A Novel Micronutrient Supplement to Preserve Male Metabolic Health and Prevent Fatty Liver (P21-007-19). (13th June 2019) - Khatiwada, Saroj; Lecomte, Virginie; Morris, Margaret; Maloney, Chris
Abstract: Objectives: Growing evidence shows detrimental effects of paternal obesity on subsequent generations. We designed a micronutrient supplement whose components participate in one carbon metabolism and are anticipated to improve antioxidant capacity. Here, we studied the effects of the supplement on metabolic health and hepatic lipid metabolism in male rats consuming either a normal healthy diet or an obesogenic diet. Methods: Male Sprague Dawley rats (3 weeks old, 17/group) were weaned onto control (CD) or high fat diet (HFD) with or without added micronutrient supplement (CDS; HFDS). After 12 weeks of diet, body composition was measured by magnetic resonance imaging, and blood samples were collected to assess supplementation levels. After 19 weeks of diet, oral glucose tolerance test (OGTT) was performed and plasma was collected to determine insulin release. At 27 weeks of diet, the rats were fasted and culled to harvest blood and tissues. Liver lipids and expression of genes involved in hepatic development and lipid metabolism were measured. Results: Supplementation was confirmed by determining plasma folate concentrations (one component of supplement), which were increased by 26% across supplemented groups. HFD increased adiposity ( P < 0.001) and body weight ( P < 0.001), both of which were normalized in the HFDS group. HFD fed animals were glucose intolerant (blood glucose during OGTT, P = 0.005) compared to CD fed animals and had to release more insulin to clear an equivalent glucose load (insulin release during OGTT, P < 0.001). In comparison, the animals consuming HFDS needed less insulin to clear an equivalent glucose load ( P < 0.001 vs HFD). HFD rats had larger livers than HFDS rats ( P < 0.001). Micronutrient supplementation reduced hepatic triglyceride accumulation ( P < 0.001) regardless of diet; this was accompanied by altered gene expression (particularly of CPT-1). Conclusions: Dietary micronutrient supplementation prevented weight gain and adiposity, improved metabolic health, and excess lipid accumulation in liver in response to HFD. This provides evidence that the micronutrient supplement can preserve health and prevent fatty liver even when animals consume an obesogenic diet. Funding Sources: NHMRC Australia project grant held by MJM and CAM. SK was supported by a UNSW international scholarship.